# Topic: Math Verify: (cos^2x)(tan^2x) + (cos^2x)= 1 Thank you in advance....

### 2 Answers | Add Yours

In trigonometry there is a major trigonometric identity as;

`sin^2x+cos^2x = 1`

We also know that;

`tanx = (sinx)/cosx`

Now we will start the question from Left Hand Side(LHS)

`LHS`

`= (cos^2x)tan^2x+cos^2x`

`= (cos^2x)(sin^2x)/(cos^2x)+cos^2x`

`= sin^2x+cos^2x`

`= 1`

`= RHS`

** So it is proven that **`(cos^2x)tan^2x+cos^2x = 1`

**Sources:**

Show `cos^2x(tan^2x)+cos^2x=1` :

`cos^2x(tan^2x)+cos^2x` Given

`=cos^2x(tan^2x+1)` Factor out common term

`=cos^2x(sec^2x)` Pythasgorean relationship

`=cos^2x*1/(cos^2x)` Definition of sec(x)

`=1` as required.